Republic of Guinea: an analysis of current drivers of change - Larcher Carvalho, A. (Noref Working Paper, 2011)
Since gaining independence from France in 1958, Guinea has remained relatively stable and has never experienced violent conflict. Until the bloodless military coup of 2008, it had had only two governments: the socialist administration of Sékou Touré (1958-1984) and the liberal regime of Lansana Conté (1984-2008). Despite some moves towards a more democratic system, including the adoption by referendum of a new constitution in 1990, the latter years of the Conté government were marked by bad governance, human rights violations, weak rule of law and impunity. This was compounded by the prolonged illness of the president, whose fitness to govern was widely doubted, and by 2003 there were fears that Guinea could become yet another failed state. The military junta headed by Captain Moussa Dadis Camara that assumed power following Conté’s death in December 2008 promised a transition to democracy but hopes were shattered on 28 September 2009 when a peaceful demonstration was brutally suppressed, leaving 150 people dead. Nevertheless, when Dadis Camara was replaced by General Sékouba Konaté following an assassination attempt, transitional institutions were established to pave the way for elections. Despite political turmoil and technical challenges, Alpha Condé, a longstanding opposition leader, was elected president in December 2010 after what were considered to be the first ever credible elections in Guinea. Successful transition The successful transition was seen as proof of Guinean society’s commitment to peace, democracy and social justice. However, social tensions, arising from both structural factors and the positions being taken by the main actors, remain and may pose obstacles or challenges to the building of democracy and social peace. This analysis examines key factors (both structural and dynamic) that could influence change or cause instability in Guinea: the forces and processes at work on the ground, the chances of resolving issues that arise, and the challenges and potential pitfalls that lie ahead. It includes information based on interviews conducted with government officials, bilateral partners and donors, multilateral organisations, NGOs, academics and the media in Conakry in May 2010. Potential problems Guinea has no history of ethnic violence but ethnic divisions were exploited by some politicians during the recent elections and some fear that further ethnic tensions will surface in the future. How to address this issue, which is linked to the power structure in Guinea, will be a challenge and requires political maturity from party leaders. Democratisation will inevitably mean dismantling existing power structures and is thus another potential source of destabilisation. Success in achieving democratisation and better governance is contingent on the economic situation. It will be difficult to plan and implement reforms that adequately address society’s demands; the size of the task and the time frame needed to implement them cannot be underestimated. Serious tension between the new government and civil society is likely in the future: social expectations are extremely high and the difficult economic and social conditions may once again fuel popular discontent. It is essential that participation and dialogue platforms between government and civil society remain open, especially in times of crisis, so that social consensus for the difficult tasks ahead can be found. Such platforms have proven effective in the past and may be instrumental in preventing a return to more authoritarian forms of government. Impunity and redress for past human rights violations will also be a major challenge for the new president. He has announced the establishment of a truth and reconciliation commission but no details are so far available. However, combating impunity in the long term will require reforming the deficient justice system as well as the security and defence sectors. The army, which for decades was the strongest institution in Guinea, has become destabilised for a number of reasons and an increase in the proliferation of light weapons and drug trafficking in urban areas further complicates the security situation. Increasingly difficult living conditions – which include rising food and fuel prices, a stagnant economy resulting mainly from the overall decline in commodity prices in the past century and Guinea’s growing debt burden – mean that, even though it is a resource-rich country, it is undergoing a deep economic and financial crisis. The growth in commodity prices (particularly bauxite) over the past few years may reverse this trend but finding ways to improve competitiveness, attract investment and stimulate the development of a private sector capable of ensuring growth and promoting exports are major tests for which there are no clear strategies. Lastly, while Guinea’s relations with its neighbours are currently stable, the spillover effects of nearby conflicts, such as the current one in Ivory Coast, continue to pose a serious risk of regional instability